2020
DOI: 10.1016/j.micpath.2020.104482
|View full text |Cite
|
Sign up to set email alerts
|

Trans-cinnamaldehyde potently kills Enterococcus faecalis biofilm cells and prevents biofilm recovery

Abstract: Enterococcus faecalis is a biofilm-forming, nosocomial pathogen that is frequently isolated from failed root canal treatments. Contemporary root canal disinfectants are ineffective in eliminating these biofilms and preventing reinfection. As a result, there is a pressing need to identify novel and safe antibiofilm molecules. The effect of short-term (5 and 15 min) and long-term (24 h) treatments of TC on the viability of E. faecalis biofilms was compared with currently used root canal disinfectants. Treatment … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 43 publications
4
25
0
Order By: Relevance
“…Tawakoli et al [ 113 ] characterized the effects of 5% sodium hypochlorite, 17% EDTA, 3% hydrogen peroxide, and 2% chlorhexidine on a three-species biofilm and reported that sodium hypochlorite eradicated the stainable matrix and bacteria in cultured biofilms, while chlorhexidine and hydrogen peroxide merely reduced bacterial cell volumes without dissolving the matrix [ 113 ]. Ali et al [ 114 ] demonstrated that a natural molecule trans-cinnamaldehyde could kill E. faecalis biofilm cells as effectively as sodium hypochlorite. Confocal microscopic characterization demonstrated largely “red” areas in the treated biofilm, implying complete bacterial killing [ 114 ].…”
Section: Clinical Implications Of Root Canal Infectionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Tawakoli et al [ 113 ] characterized the effects of 5% sodium hypochlorite, 17% EDTA, 3% hydrogen peroxide, and 2% chlorhexidine on a three-species biofilm and reported that sodium hypochlorite eradicated the stainable matrix and bacteria in cultured biofilms, while chlorhexidine and hydrogen peroxide merely reduced bacterial cell volumes without dissolving the matrix [ 113 ]. Ali et al [ 114 ] demonstrated that a natural molecule trans-cinnamaldehyde could kill E. faecalis biofilm cells as effectively as sodium hypochlorite. Confocal microscopic characterization demonstrated largely “red” areas in the treated biofilm, implying complete bacterial killing [ 114 ].…”
Section: Clinical Implications Of Root Canal Infectionsmentioning
confidence: 99%
“…Ali et al [ 114 ] demonstrated that a natural molecule trans-cinnamaldehyde could kill E. faecalis biofilm cells as effectively as sodium hypochlorite. Confocal microscopic characterization demonstrated largely “red” areas in the treated biofilm, implying complete bacterial killing [ 114 ]. However, when the same authors characterized the polysaccharide matrix component, they discovered that trans-cinnamaldehyde could not eliminate the matrix.…”
Section: Clinical Implications Of Root Canal Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…When used in the management of biofilms of S. mutans, the essential oil from C. zeylanicum skin was able to inhibit their formation by up to 99%, at a concentration of 0.224 mg•mL −1 [131]. β-linalool and (E)-cinnamaldehyde are the two main compounds present in this oil, and can be pointed out as responsible for its antibiofilm properties [132,133]. In addition, the essential oils of Coriandrum sativum L., a medicinal plant with nutritional benefits, commonly named coriander, exhibit antibacterial and antibiofilm properties against S. mutans, in addition to holding antioxidant and anesthetic properties [134,135].…”
Section: The Most Promising Medicinal Plant Extracts In the Control Of Oral Biofilmsmentioning
confidence: 97%